Calling phenology and detectability of a threatened amphibian (Litoria olongburensis) in ephemeral wetlands varies along a latitudinal cline: Implications for management. (29th April 2016) - Lowe, Katrin; Castley, J. Guy; Hero, Jean‐Marc
Abstract: Amphibian reproductive biology and activity are highly sensitive to environmental cues. For amphibian conservation in the face of climate change, a clear priority is to investigate impacts of variable weather on breeding activity and detectability. This study assessed variation in the phenology, intensity and detectability of calling for a threatened temporary wetland breeding species, Litoria olongburensis . Acoustic and visual surveys were conducted monthly from August 2009 to July 2011 over the species latitudinal range in eastern Australia. Calling phenology of L. olongburensis varied spatially and temporally within and among latitudinal clusters. Detectability of frogs also varied among months and transects, and also with the type of survey conducted (visual vs. acoustic). Air temperature was a strong predictor for the onset of the calling season (early spring); however, peaks in calling abundances were primarily driven by monthly accumulated rainfall. The duration of the calling season varied among latitudinal clusters, becoming narrower moving south, reflecting clinal variation in weather patterns. This study presents a framework for amphibian species management using a combination of survey techniques and the climatic conditions influencing detectability. Applied along the latitudinal gradient, it provides data for predicting the likely impacts of climate change on amphibian activity and reproduction.